2019
DOI: 10.1128/jvi.01154-19
|View full text |Cite
|
Sign up to set email alerts
|

Modified Vaccinia Virus Ankara Can Induce Optimal CD8+T Cell Responses to Directly Primed Antigens Depending on Vaccine Design

Abstract: Recombinant vaccines based on vaccinia virus and particularly attenuated strains such as MVA are in human clinical trials, but due to the complexity of these large vectors much remains to be understood about the design parameters that alter their immunogenicity. Previous work had found that MVA vectors should be designed to express stable protein in order to induce robust immunity by CD8+ (cytotoxic) T cells. Here, we found that the primacy of stable antigen is not generalizable to all designs of MVA and may d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 94 publications
0
15
0
Order By: Relevance
“…Although comparative (side by side) experiments might be needed, it is reasonable to speculate that the different source of MVA vector and/or the different locus/ promoter used in this work could explain the improved immunogenicity against the encoded RVFV glycoprotein antigens. In this sense, it has been described that genome location and TK function can contribute to the relative immunogenicity of antigens when expressed from rMVA 45 . In addition, in previous rMVA-GnGc vaccine construct 10 , the heterologous gene was cloned under the control of the vaccinia 7.5 k early/late promoter, while in the MVA-GnGc-NS1 describe here the RVFV glycoproteins genes were placed under the control of an optimized strong early/ late promoter 46,47 .…”
Section: Discussionmentioning
confidence: 99%
“…Although comparative (side by side) experiments might be needed, it is reasonable to speculate that the different source of MVA vector and/or the different locus/ promoter used in this work could explain the improved immunogenicity against the encoded RVFV glycoprotein antigens. In this sense, it has been described that genome location and TK function can contribute to the relative immunogenicity of antigens when expressed from rMVA 45 . In addition, in previous rMVA-GnGc vaccine construct 10 , the heterologous gene was cloned under the control of the vaccinia 7.5 k early/late promoter, while in the MVA-GnGc-NS1 describe here the RVFV glycoproteins genes were placed under the control of an optimized strong early/ late promoter 46,47 .…”
Section: Discussionmentioning
confidence: 99%
“…which most likely differ for each ligand. As recently shown ( 64 ), there may be variations between vaccinia virus vaccine delivery platforms such as replication-competent vs. -deficient viruses, different insertion loci for target gene expression or the presence/absence of viral thymidine kinase by which immunodominance can be shaped to a certain degree, but it will not be reversed even in the absence of the immunodominant B8 epitope ( 49 ). In contrast to the systemic i.p.…”
Section: Discussionmentioning
confidence: 99%
“…We started this investigation by following up a previous study that found that VACV virion proteins were overrepresented among immunogenic antigens in mice immunized with infected cells. These experiments used recombinant vaccines based on VACV strain WR, but wild-type virus was not tested and infected cells were injected by the intraperitoneal route ( 22 , 24 ). In our first experiment, MHC-mismatched cells were infected with VACV WR for a total of 6 h, inactivated by heating to 60°C for an hour (here referred to as heat inactivated [HI]), and then used to immunize groups of mice by intradermal injection ( 25 ).…”
Section: Resultsmentioning
confidence: 99%
“…In our first experiment, MHC-mismatched cells were infected with VACV WR for a total of 6 h, inactivated by heating to 60°C for an hour (here referred to as heat inactivated [HI]), and then used to immunize groups of mice by intradermal injection ( 25 ). This published treatment eliminates infectivity and de novo viral gene expression and presentation in vivo , as shown by the complete loss of responses to VACV-encoded minimal epitope constructs that require direct presentation to prime CD8 + T cells ( 22 , 24 ). The CD8 + T cell response to a well-characterized panel of major VACV epitopes was then measured at the peak of the acute response by ex vivo stimulation of splenocytes with synthetic peptides and intracellular staining for gamma interferon (IFN-γ) ( 19 , 26 28 ).…”
Section: Resultsmentioning
confidence: 99%